2018
DOI: 10.1089/neu.2017.5225
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy in the Treatment of Acute Severe Traumatic Brain Injury: A Systematic Review

Abstract: There has been no major advancement in a quarter of a century for the treatment of acute severe traumatic brain injury (TBI). This review summarizes 40 years of clinical and pre-clinical research on the treatment of acute TBI with hyperbaric oxygen therapy (HBO) in the context of an impending National Institute of Neurologic Disorders and Stroke-funded, multi-center, randomized, adaptive Phase II clinical trial -the Hyperbaric Oxygen Brain Injury Treatment (HOBIT) trial. Thirty studies (eight clinical and 22 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Enhanced oxygen supply and increased pressure result in a wide variety of pathophysiological mechanisms. Thus, HBOT is believed to diminish neuroinflammatory responses, blood-brain barrier permeability and apoptosis while positively impacting neurogenesis, neuronal and axonal integrity and synaptogenesis (reviewed by Daly et al, 2018;Fischer et al, 2010). All of these effects may potentially influence patients' cognitive functioning.…”
Section: Key Pointsmentioning
confidence: 99%
“…Enhanced oxygen supply and increased pressure result in a wide variety of pathophysiological mechanisms. Thus, HBOT is believed to diminish neuroinflammatory responses, blood-brain barrier permeability and apoptosis while positively impacting neurogenesis, neuronal and axonal integrity and synaptogenesis (reviewed by Daly et al, 2018;Fischer et al, 2010). All of these effects may potentially influence patients' cognitive functioning.…”
Section: Key Pointsmentioning
confidence: 99%
“…However, the efficiency of HBO therapy remains extremely controversial 57. Several studies have reported that HBO therapy improved the neurological deficits and cognitive impairments of patients in the acute phase of severe TBI 8,9. In contrast, other studies have demonstrated that HBO therapy had no effect on patients with mild and chronic TBI 10.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, a neurosurgery clinical team from the University of Minnesota published a review on the treatment of acute TBI with HBO that collected and analyzed 30 clinical and animal research articles. Their results showed clear e cacy of HBO in the treatment of acute TBI [14]. Preliminary studies of our group also con rmed that HBO treatment can reduce secondary injury after TBI, and its mechanism of action may be related to the reduction of cerebral edema, inhibition of astrocyte proliferation, improvement of brain metabolism, and inhibition of neuroin ammation [15][16][17].…”
Section: Introductionmentioning
confidence: 68%